Interactive resources used in research interviewing - Grindsted, Anette (HERMES - Journal of Language and Communication in Business, 2004)
The semi-structured research interview is often criticized for not producing reliable and valid results due to 1) interviewer bias, and 2) non-commitment on the part of the informants, and 3) for being an expensive information gathering tool. By applying a CA perspective in the analysis of semi-structured interview data it is shown, however, that in the present case both interviewers and informants were very much concerned with producing true, accurate and valid responses. It is shown that among the interactive resources they have at their disposal, some of them are especially suited to ensure validity and are often recurred to by both parts. They concern e.g. question-response managment, the management of pauses, and repair organization. That the semi-struc tured research interview is an expensive information gathering tool cannot be denied. However, and all other things being equal, if validity is secured, it may turn out be a more safe research instrument than the structured interview.